1999
DOI: 10.1063/1.593726
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic regimes of antiferromagnetic resonance in a quasi-two-dimensional easy-axis antiferromagnet (NH3)2(CH2)4MnCl4

Abstract: Chaotic regimes of the microwave energy absorption are experimentally observed and analyzed for two-dimensional metallorganic antiferromagnet (NH 3 ) 2 (CH 2 ) 4 MnCl 4 at low temperatures under the conditions of nonlinear antiferromagnetic resonance. Relaxation oscillations of energy absorption are investigated in detail. Their frequency spectra, frequency-amplitude characteristics, and dependences of absorbed power on driving power and static magnetic field are studied. It is shown that the dynamics of relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…In the case of M = Mn, Cu, and Cd, the crystal structures consist of an alternate octahedron (MX 6 ) 2– and organic chains. In the case of M = Co and Zn, isolated tetrahedral structures are formed, where an inorganic layer of (MX 4 ) 2– is sandwiched between the layers of an organic cation. Perovskite compounds composed of [NH 3 (CH 2 ) n NH 3 ] cations and MX 4 anions are zero-dimensional, whereas those containing MX 6 anions are two-dimensional. Furthermore, several studies focusing on their molecular structure have reported even–odd effects as the number of carbon atoms in the diammonium chain changes, which affects the structural properties of these materials .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of M = Mn, Cu, and Cd, the crystal structures consist of an alternate octahedron (MX 6 ) 2– and organic chains. In the case of M = Co and Zn, isolated tetrahedral structures are formed, where an inorganic layer of (MX 4 ) 2– is sandwiched between the layers of an organic cation. Perovskite compounds composed of [NH 3 (CH 2 ) n NH 3 ] cations and MX 4 anions are zero-dimensional, whereas those containing MX 6 anions are two-dimensional. Furthermore, several studies focusing on their molecular structure have reported even–odd effects as the number of carbon atoms in the diammonium chain changes, which affects the structural properties of these materials .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, organic-inorganic hybrid [NH 3 (CH 2 ) 6 NH 3 ]ZnCl 4 single crystals replacing with eco-friendly were grown using the aqueous solution method, and their crystal structures, phase transition temperatures (T C ), and thermal properties were studied. The effect of temperature on coordination geometry, which can provide valuable insights into the physical and chemical properties of compounds, was discussed based on information obtained from 1 H, 13 C, and 14 N nuclear magnetic resonance (NMR) chemical shifts. The energy transfer was investigated by employing the spin-lattice relaxation time (T 1ρ ).…”
Section: Introductionmentioning
confidence: 99%
“…The properties depend on factors such as the characteristics of organic cations and geometry of the inorganic metal halide anions ((MX 6 ) 2– or (MX 4 ) 2– ) constituting the crystal. When M = Mn, Cu, and Cd, the crystal structures consist of alternate octahedron (MX 6 ) 2– and organic chains. In contrast, when M = Co and Zn, isolated tetrahedral structures are formed, where an inorganic layer of (MX 4 ) 2– is sandwiched between layers of an organic cation. The ammonium ions bonded at both ends of the organic chain combine with the halide ions in the inorganic layer and stabilize the layered structure by forming N–H···X hydrogen bonds. The organic chains extend along the a -axis.…”
Section: Introductionmentioning
confidence: 99%